2016
DOI: 10.5194/acp-16-1713-2016
|View full text |Cite
|
Sign up to set email alerts
|

Continuous measurements at the urban roadside in an Asian megacity by Aerosol Chemical Speciation Monitor (ACSM): particulate matter characteristics during fall and winter seasons in Hong Kong

Abstract: Abstract. Non-refractory submicron aerosol is characterized using an Aerosol Chemical Speciation Monitor (ACSM) in the fall and winter seasons of 2013 on the roadside in an Asian megacity environment in Hong Kong. Organic aerosol (OA), characterized by application of Positive Matrix Factorization (PMF), and sulfate are found to be dominant. Traffic-related organic aerosol shows good correlation with other vehicle-related species, and cooking aerosol displays clear mealtime concentration maxima and association … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 56 publications
5
47
1
Order By: Relevance
“…Higher EC concentrations were typically associated with rush hour traffic and confirm the local nature of EC and its relation to mainly on-road traffic Cheng et al, 2010;Huang et al, 2014;Louie et al, 2005). While earlier studies (samples dated pre-2005) reported EC concentrations in the range of 11-25 µg C m −3 in PM 2.5 at the open roadside (Louie et al, 2005;Cheng et al, 2010;Lee et al, 2006), more recent measurements (2012-2013) indicate a significant reduction in overall roadside EC burdens with concentrations ∼ 5 µg C m −3 Sun et al, 2016;. Vehicle-related concentrations at a roadside measurement site were estimated to ∼ 2 and ∼ 7 µg m −3 of OC and carbonaceous aerosol, respectively, in 2012, accounting for one-third of total OC in PM 2.5 and one-quarter of total PM 2.5 .…”
Section: Background Of Vehicle Emission Studies In Hong Kongmentioning
confidence: 53%
See 3 more Smart Citations
“…Higher EC concentrations were typically associated with rush hour traffic and confirm the local nature of EC and its relation to mainly on-road traffic Cheng et al, 2010;Huang et al, 2014;Louie et al, 2005). While earlier studies (samples dated pre-2005) reported EC concentrations in the range of 11-25 µg C m −3 in PM 2.5 at the open roadside (Louie et al, 2005;Cheng et al, 2010;Lee et al, 2006), more recent measurements (2012-2013) indicate a significant reduction in overall roadside EC burdens with concentrations ∼ 5 µg C m −3 Sun et al, 2016;. Vehicle-related concentrations at a roadside measurement site were estimated to ∼ 2 and ∼ 7 µg m −3 of OC and carbonaceous aerosol, respectively, in 2012, accounting for one-third of total OC in PM 2.5 and one-quarter of total PM 2.5 .…”
Section: Background Of Vehicle Emission Studies In Hong Kongmentioning
confidence: 53%
“…While most previous studies have evaluated traffic exhaust contributions in confined environments (tunnels), focal locations (e.g., bus terminus, taxi stand) or by plume chase, this work provides a quantitative estimation of vehicle exhaust related carbonaceous aerosol contributions and their relationship to traffic flow characteristics from ambient measurements in a more complex urban environment. We aim B. P. Lee et al: Evaluation of traffic exhaust contributions to ambient carbonaceous submicron PM to complement previous studies which only estimated overall traffic-related aerosol contributions from online and offline ECOC measurements at different time resolutions (from hourly to 24 h samples) (Louie et al, 2005;Huang et al, 2014) and online mass spectrometric methods (Sun et al, 2016;Lee et al, 2015) at the same location by combining resolved traffic-related organic aerosol concentrations from factor analysis of aerosol mass spectrometer (AMS) data, online EC measurements and traffic count data to gain an improved understanding of the influence of traffic composition on traffic-related submicron carbonaceous aerosol.…”
Section: Background Of Vehicle Emission Studies In Hong Kongmentioning
confidence: 94%
See 2 more Smart Citations
“…The leading sources of ambient and household air pollution vary on the basis of regional economic development. In more developed urban regions, such as Beijing and Hong Kong, ambient air pollution is due largely to vehicle‐ and industry‐related emissions, whereas household air pollution results mostly from the infiltration of ambient PM. In less developed rural regions, levels of both ambient and household air pollution are driven mostly by biomass fuel burning .…”
Section: Sources Of Air Pollution In the Ap Regionmentioning
confidence: 99%